Colour and textural typologies of goat cream butter with sea buckthorn (Hippophae rhamnoides L.) puree : instrumental, sensory, and consumer input for product development - Chudy, Sylwia (Array, 2021)
In this research the effect of the addition of sea buckthorn puree (Hippophae rhamnoides L.) to goat cream butter was examined via analysis of its textural, physicochemical and sensory properties. Consumer acceptance was assessed. The addition of sea buckthorn promoted a stickiness and acidic flavour compared to the original goat butter. The number of consumers who liked goat butter increased by 35 %. The optimal amount of sea buckthorn added was determined as 1.5 %. A larger amount had a negative effect on the colour, as well as creating a more acidic flavour and fruit aroma.